Methodology for Estimating Communication Reliability in Shortwave Radio-Frequency Transmission Channels with Rician Fading Given Ionospheric Diffusivity - V. P. Pashintsev; D. A. Belokon; S. A. Koval; A. D. Skorik (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. There exists a technique for estimating the dependence of communication reliability in a shortwave radio-frequency transmission channel (SWRC) with a single discrete beam and diffuse wave scattering across small-scale ionospheric inhomogeneities on the selected operating frequency taking into account the given signal-to-noise ratio and ionospheric diffusivity. In this technique, the Nakagami m-distribution is used to describe interference fading of the received signal. However, in a single-beam SWRC, fading signal amplitudes are described by the Rician or generalized Rayleigh, rather than by Nakagami, distribution in 90 % of all cases. At the same time, the results obtained using the Nakagami distribution to approximate fading and to assess its effect on communication quality agrees well with those obtained by the Rician distribution only in two cases: the presence of Rayleigh distribution or the complete absence of fading.Aim. To develop a methodology for estimating communication reliability in a single-beam SWRC with Rician fading and to compare its results with that under Nakagami fading.Materials and methods. The effect of operating frequency and ionospheric diffusivity on fading distribution parameters in a single-beam SWRC was estimated by simulating transionospheric communication channels based on a radio-physical phase screen method. The effect of Rician fading parameters on communication reliability was simulated in the MatLab environment. The initial data on ionospheric parameters were obtained using the IRI-2016 model.Results. A three-stage methodology for estimating communication reliability in a single-beam SWRC with Rician fading was developed; its results were compared with that under Nakagami fading. Dependencies were obtained to describe communication reliability in a single-beam SWRC during the day and at night on the selected operating frequency relative to the maximum applicable frequency and on the level of ionospheric diffusivity during Rician and Nakagami fading.Conclusion. The conducted analysis showed that, at different levels of ionospheric diffusivity, communication reliability in a single-beam SWRC with Nakagami fading can be significantly overestimated (up to 12 %), compared to that under Rician fading.